Protection of Hot News under the Broadcasting Laws in India (Journal of Intellectual Property Rights (JIPR), 2024)
Hot news has enormous value and as the name itself describes, it is new as well as hot which makes it highly exploitativecommercially. The growing economic significance of the broadcast industry has intensified the competition among thebroadcasters to exploit hot news. The craving for hot news amongst the masses sometimes stirs the competitors to free ride over the efforts of the original gatherer. The disputes arising out of this fact led to the birth of “doctrine of hot news'' in the United States of America, which injuncted the free rider from misappropriating the hot news. Indian courts acknowledged this doctrine protecting the broadcasting organisations until 2013 when the position was overturned and dissemination of the hot news by free riders was legitimised. To understand the present as well as the correct position of hot news, the actual character of hot news and its relevance, the paper analyses the broadcasting laws of India vis-a-vis the protectability of hot news. The research finds that various laws, having a bearing on the Broadcasting Sector, including Copyright Act, Contract Act, Tort Law along with the Constitution of India contain enough provisions for protection of hot news.